AN ANALYSIS OF CODE MIXING IN PEKANBARU BILLBOARD ADVERTISEMENT (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The study aimed to analyze the form of code mixing used in Pekanbarubillboard advertisement and to find out the dominant English lexical categories inPekanbaru billboard advertisement. This research is qualitative research withdescriptive analysis methods to find the percentage of data. The source of the data inthis research is from billboard advertisement in Pekanbaru. The researcher collected atotal of 45 billboard advertisement data. Data is collected by study documents becausethe data source is obtained from written form (billboard a advertisement). Based on thefindings, researchers confirmed that most forms of code mixing are words while thedominant category of the Lexical Category of English is nouns. As a result, the totalnumbers of words are forty five (45). In addition, the researcher discovers that “Covid-19”, “YouTube”, and “Hype” are English words that mostly appear in Pekanbarubillboard advertisement.The researchers' findings present that the two forms of codemixing are words (such as; nouns, adjectives, verbs, pronouns and prepositions), andidioms. Therefore, the researcher confirms that there is a code mixing that is added byadvertiser into Pekanbaru billboard advertisement.Key Words: Code Mixing, Billboard, Advertisment.